The Influence of Religious Understanding, Family Environment, and Emotional Intelligence on Students’ Religious Practices - Mely Cahyani; Khairil Anwar; Tohirin Tohirin (Edusoshum : Journal of Islamic Education and Social Humanities, 2026)
The phenomenon behind this study is the lack of consistency in students' worship behavior despite having received Islamic Religious Education at school. This condition shows that students' worship behavior is not only influenced by religious understanding, but also by family environment and internal psychological factors. This study aims to analyze the relationship and influence of religious understanding, family environment, and emotional intelligence on students' worship behavior. The research was conducted at MTs with a population of 66 students, who were also used as samples through total sampling technique. This study is a field survey with a correlational quantitative approach. Data collection was conducted using a Likert scale questionnaire, namely a questionnaire on religious understanding (10 items), family environment (10 items), emotional intelligence (10 items), and students' worship behavior (10 items). Data analysis was performed using correlation and multiple regression tests. The results showed that religious understanding had a positive and significant relationship with students' worship behavior (r = 0.634; p < 0.05), family environment also showed a positive and significant relationship (r = 0.549; p < 0.05), and emotional intelligence had the strongest relationship with students' worship behavior (r = 0.829; p < 0.05). The regression analysis results show that religious understanding, family environment, and emotional intelligence simultaneously have a significant effect on students' worship behavior with a coefficient of determination of R² = 0.714, which means that 71% of the variation in students' worship behavior can be explained by these three variables. This study is expected to serve as a basis for the development of integrated student worship guidance through the strengthening of cognitive, family, and emotional intelligence aspects.